Pathways to Engagement: An Exploratory Qualitative Analysis of Factors That Facilitate Men’s Engagement in IPV Intervention Programs - Bouchard, Jessica (Violence against women, 2021)
Research on intimate partner violence (IPV) interventions has long indicated mixed support for their effectiveness at reducing abusive behaviors. Limited prior research has focused on factors associated with participant engagement in the treatment process. Using a qualitative thematic analysis and a sample of 180 participants who completed an IPV intervention program, the purpose of this study was to identify key factors that facilitate men’s responsiveness to IPV intervention programs. The findings highlight several commonalities in participants’ perceptions of pathways that facilitated and/or hindered their engagement in the treatment process, and provide insights into how program/process elements can be structured to enhance engagement.